English for secretaries (Oxford Univ. Press, 1995)
This book is an immediate language course designed to help the foreign secretary who needs English in order to function efficiently and confidently in her job. It includes practice in pronunciation; remedial grammar exercises and drills; situational dialogues; and rhythm, intonation and stress exercises.